Análise da política nacional de resíduos sólidos como marco regulatório provedor de mudanças no arcabouço legal dos entes federados - Marotti, Ana Cristina Bagatini (2018)
The National Policy of Solid Waste (NPSW), established by Law nº 12,305 of 2010, is the principal policy on solid waste management in the country. The intention of this dissertation is to evaluate the NPSW as a regulatory mark that provides changes in the legislations of the three levels of government, national, state and municipal, until the year 2017. The methodological aspects included documentary analyzes of the national normative and legal framework for solid waste management and before the validation the expert panel method; analyzes of the state solid waste policies published; and a case study in the municipality of Rio de Janeiro referring to municipal legislation. The selection of the municipality was due to the easiness of access and availability to its legal framework and the national importance that the municipality represents. These analyzes are based on transformations of these frameworks, national and municipal, and the state policies against the NPSW’s publication. The results showed that NPSW is a mark for solid waste management and that it was, in part, a provider of changes in the legal framework of the federated entities, because the current national framework is consisted by 77% of legal parts published until 2009, and 23% after this year which have influenced the content established by the NPSW. Despite the changes resulting from the NPSW, some institutions provided by law do not correspond to norms and regulations, impacting on their effectiveness. About the state policies, 30% were published after 2010, or underwent updates to suit national policy, but 26% of states do not yet have their own policies. In the city of Rio de Janeiro, the PMGIRS was published after the promotion of the NPSW, although it presented laws and decrees that encouraged the creation of a plan in pre-2010 years. Thus, the NPSW as a normative and regulatory framework was responsible for providing some changes in the national, state and municipal legal frameworks, but still presenting weaknesses in its execution.